Implementation of lean thinking through A3 report in plastic injection company - Sartika Rini (International Journal of Industrial Optimization, 2021)
Lean thinking, or lean production, which has long been introduced by Toyota, is a process improvement concept that is carried out by eliminating waste and focusing more on things that create values. Its emergence was inspired by the fact on the production floor, where only a small fraction of the total times and efforts contributed to creating added value to customersâ€™ final product. Lots of prior studies have shown various benefits of implementing lean production, especially in manufacturing industries. However, many companies still find difficulties trying to implement a lean approach for the first time. Furthermore, they do not have a clear and concise picture of each component of the lean approach they want to apply. This company is based on case study which has many rejected products so that it makes higher production cost. Therefore, this study proposed an implementation of lean thinking to reduce the number of rejected products through A3 report. This result show the defects can be reduced and the standard operational procedure has been developed.Â